Exploring supply chain capabilities in textile-to-textile recycling – A European interview study - Erik Sandberg; Rudrajeet Pal (Cleaner Logistics and Supply Chain)
In light of the recent developments in recycling technologies and commercialization, supply chain capabilities are decisive for large-scale textile-to-textile recycling practices. Despite this, the current status and landscape of these practices is surprisingly little researched from a logistics and supply chain management point of view. Therefore, the purpose of this study is to explore supply chain capabilities required in the textile-to-textile recycling supply chain. The paper is based on an interview study with 20 stakeholders along the textile recycling supply chain, covering various types of collectors, sorters, and recyclers in Sweden and mainland Europe.The findings present eleven specific supply chain capabilities distributed over the three main supply chain activities of collection, sorting, and recycling. By doing this, the study seeks to provide a more thorough and comprehensive understanding of the role of logistics and supply chain management in textile-to-textile recycling practices. The findings also provide insights into more general industry-related design issues, including the matching of product supply and demand, the establishment of new supply chains, and balancing global and local interests.